Ethics and Justice in Learning Analytics. Issue 179 (September 2017) - Johnson, Jeffrey Alan
Abstract : The many complex challenges posed by learning analytics can best be understood within a framework of structural justice, which focuses on the ways in which the informational, operational, and organizational structures of learning analytics influence students' capacities for self‐development and self‐determination. This places primary responsibility for ethical use of learning analytics on institutions rather than on users.